Analisis Kesulitan Membaca Permulaan pada Siswa Kelas I di SDN 14 Sungai Raya - Saputri, Wulanda; Afryaningsih, Yunika; Fathonah, Iir Nikmatul (Indo-MathEdu Intellectuals Journal, 2025)
This study was motivated by preliminary findings from interviews with classroom teachers, which showed that some first-grade students at SDN 14 Sungai Raya still had difficulty with early reading. These difficulties included the ability to string together vowels, distinguish between letters that are similar in shape, such as b, d, p, n, m, v, and w, and read syllables consisting of more than three letters. Based on these conditions, this study aims to analyze the forms of difficulty in early reading among first-grade students at SDN 14 Sungai Raya. The method used is qualitative research with a descriptive approach. Data were collected through early reading tests covering aspects of letter recognition, reading meaningful and meaningless words, reading aloud, reading comprehension, and listening. The research subjects consisted of 18 students, namely 8 boys and 10 girls. The data obtained were analyzed descriptively by grouping the test results according to the students' reading ability categories. The results showed that most students still had difficulty recognizing letters, tended to read by spelling, and experienced difficulties in reading meaningless words. In addition, their reading aloud and reading comprehension skills were still low, while their listening skills varied among students.